2018
DOI: 10.1093/mmy/myy119
|View full text |Cite
|
Sign up to set email alerts
|

Potassium iodide and miltefosine inhibit biofilms of Sporothrix schenckii species complex in yeast and filamentous forms

Abstract: This study aimed to evaluate the yeast biofilm growth kinetics and ultrastructure of Sporothrix schenckii complex and assess their mature biofilm susceptibility in filamentous and yeast forms to potassium iodide (KI) and miltefosine (MIL). Yeast biofilms were evaluated by crystal violet staining, XTT reduction assay and microscopic techniques. Susceptibility of planktonic and sessile cells was analyzed by broth microdilution. S. schenckii complex in yeast form produced biofilms, with an optimum maturation at 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
0
14
0
4
Order By: Relevance
“…Potassium iodide is also recommended for the treatment of cat cases refractory to itraconazole (in those presenting nasal mucosal lesions and respiratory signs) [235]. The precise mechanism by which potassium iodide acts is still unknown [236], although Brilhante et al [237] recently reported the efficacy of this drug in inhibiting biofilm formation of Sporothrix cells, grown in the planktonic state and mature biofilms in both filamentous and yeast forms. Itraconazole is the drug of choice for treatment in humans (100-200 mg/day orally) and cats (8.3-27.7 mg/kg/day) [151,166,238], but other azoles (e.g., posaconazole) as well as other antifungal classes, such as allylamine (terbinafine) and polyene (amphotericin B), may be employed depending on the clinical factors and condition of the patient's immune system.…”
Section: Therapymentioning
confidence: 99%
“…Potassium iodide is also recommended for the treatment of cat cases refractory to itraconazole (in those presenting nasal mucosal lesions and respiratory signs) [235]. The precise mechanism by which potassium iodide acts is still unknown [236], although Brilhante et al [237] recently reported the efficacy of this drug in inhibiting biofilm formation of Sporothrix cells, grown in the planktonic state and mature biofilms in both filamentous and yeast forms. Itraconazole is the drug of choice for treatment in humans (100-200 mg/day orally) and cats (8.3-27.7 mg/kg/day) [151,166,238], but other azoles (e.g., posaconazole) as well as other antifungal classes, such as allylamine (terbinafine) and polyene (amphotericin B), may be employed depending on the clinical factors and condition of the patient's immune system.…”
Section: Therapymentioning
confidence: 99%
“…MIC, minimum inhibitory concentration. and 10-50× MIC (40-200 µg/ml), respectively (Vila et al, 2013;Brilhante et al, 2019). Interestingly, Scedosporium and Lomentospora preformed biofilms were affected in the presence of 4× and 8× MIC of miltefosine, which represents 16 and 32 µg/ ml, respectively, indicating that it could be more susceptible compared with other pathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…The SMIC50 values were higher than the MICs of planktonic susceptibility, demonstrating the increased tolerance of biofilms to these drugs. Despite forming biofilms in both forms, biofilms of filamentous forms are more complex and have more layers than yeast biofilms of Sporothix species [6]. In addition, the filamentous form is responsible for maintaining the biological cycle of dissemination of this fungus, so the effect of statins on this form of growth was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In order to establish themselves in the host organism, fungi have several virulence factors, including the ability to form biofilms, which are composed of cells that form microcolonies attached to a substrate recognized by the extracellular matrix, which allows or detects whether the microorganism is in a hostile or protected environment regarding host immune defence [3][4][5]. Among the virulence factors that contribute to the survival of S. schenckii complex species, biofilm formation has been described for both filamentous and yeast forms [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%